The Effects of advertising and the effectiveness on sales of Jollibee - Dela Cruz, Rose Ann G. (Manila : National University, 2007)
The pervasiveness of advertising, its phenomenal growth as an industry, and its increased power to influence our behavior and help shape our decisions, have made advertising the object of much cristicism.
Chapter 1. Introduction -- Chapter 2. Research Design -- Chapter 3. Results and Discussions -- Chapter 4. Summary -- Appendices.
Research Design : Descriptive Method
Includes bibliographical references.
Keywords: SALES